Impact of endometriotic cystectomy on ovarian reserve function and ovulation induction outcomes in women with endometriosis undergoing assisted reproductive technology - Li, Yutao; Gong, Yu; Jiang, Haiyan; Ji, Meng (Frontiers in Endocrinology, 2026)
BackgroundThis study aims to evaluate the impact of endometriotic cysts and prior ovarian endometriotic cystectomy on ovarian reserve function in women with endometriosis undergoing assisted reproductive technology.MethodsIn this retrospective cohort study, 3,517 endometriosis patients receiving in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) between January 2016 and April 2022 were reviewed. Participants were stratified into three groups: Group A (control, n=494): patients without endometriosis undergoing IVF/ICSI for male factor infertility; Group B (non-surgical, n=217): endometriosis patients with untreated endometriotic cysts; Group C (surgical, n=122): endometriosis patients with prior cystectomy. Antral follicle count (AFC), follicle-stimulating hormone (FSH), anti-Müllerian hormone (AMH), gonadotropin (Gn) dose, number of retrieved oocytes, number of mature metaphase II (MII) oocytes and the proportion of patients with diminished ovarian reserve (DOR; AMH<1.1ng/ml) were compared across groups.ResultsOvarian reserve markers were highest in Group A [AMH: 2.88 (1.64–4.45) ng/mL; AFC: 13 (8.5–17)], followed by Group B [AMH: 2.70 (1.59–4.05) ng/mL; AFC: 11 (7–16)], with both significantly exceeding Group C [AMH: 1.97 (1.02–3.05) ng/mL; AFC: 10 (4–15)] (all P < 0.01). The incidence of DOR was significantly higher in Group C (26.23%) than in Group A (13.56%) and Group B (12.90%) (P < 0.05). The total Gn dose was significantly higher in Groups B and C than in Group A. The number of retrieved oocytes and MII oocytes did not differ significantly between Groups A and B, but both were significantly higher than in Group C (P < 0.01).ConclusionsA history of endometriotic cystectomy is associated with significantly diminished ovarian reserve and poorer ovarian response during controlled ovarian stimulation. These findings highlight the importance of individualized surgical decision-making for reproductive-aged women with endometriomas, weighing potential benefits against the risk of iatrogenic damage to ovarian function.